Digital Transformation: Optimizing Digital Population Identity Activation Services (IKD) in Kuningan Regency - Wahyuni, Yuyun; Alam, Aditya Purnama; Heryanto, Yanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Indonesian government has launched Digital Population Identity (IKD) as a step towards digitalization in the field of population administration. Kuningan Regency in West Java is one of the regions that has optimized IKD activation services. However, further assessment is needed to assess the extent to which the implementation of IKD activation has reached optimal. Based on the findings of the analysis, it shows that the IKD activation service has not reached all levels of society evenly and there are still limitations in existing facilities and infrastructure. Another challenge is the low public awareness of IKD ownership and lack of understanding of technology, especially among the elderly or people who have a low level of digital literacy. This research was conducted at the Population and Civil Registration Office of Kuningan Regency using a qualitative approach. This study uses the theory put forward by Machfud Sidik in (Maulidya & Widiyarta, 2024) which specifically focuses on three key elements: purpose, alternative decisions, and disposition. The data collection technique in this study is through observation, interviews, and documentation at the research site. This research aims to provide deeper insights related to optimizing IKD activation services and overcoming population administration challenges in the digital era.